Hukum Hak Asuh Anak Dibawah Umur dalam Masyarakat Adat Karo di Desa Paribun, Kecamatan Barus Jahe, Kabupaten Karo, Sumatera Utara - Muhammad Hajatoleslam Siregar; Mhd. Amar Adly; Heri Firmansyah (Student Research Journal, 2025)
This research analyzes the custody rights of minor children due to the termination of their parents' marriage relationship with references to the Marriage Law, the Compilation of Islamic Law and the application of Karo customary law. The research method used in this research is normative juridical. The research location is in the Paribun area, Barusjahe sub-district, Karo district, North Sumatra. The right to care for children in Article 45 of Law Number 1 of 1974 Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law explains that if the child is still not yet mumayyiz child care is assigned to the mother, when the child is mumayyiz it can be given the right to child. to decide whether to be raised by father or mother. The Law on Marriage states that fathers and mothers as guardians are obliged to take good care of their children. Parents' obligations to their children have 2 (two) commitments, namely nurturing and educating. Caring means providing support for children, such as clothing, food and shelter. Educating means providing teaching to children, whether given specifically by parents through good guidance and direction, or given formally through sending children to school. Parents' obligations to their children will not end with the dissolution of the parents' marriage, because the dissolution of the marriage is either due to live divorce, death divorce, or due to court execution. Batak customary law in raising children is based on a patrilineal framework with the condition that the child will carry on the clan from the father's line, thus child care is borne by the father.